Behavioral Counseling: Assertiveness Training Techniques to Increase Achievement Motivation and the Need to Express Oneself - Ahmad Khotibul Umam; Putu Ari Dharmayanti; Nyoman Dantes; Ni Ketut Suarni (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Students' achievement motivation and courage in expressing their potential in the school environment are still low. This study aims to evaluate the effectiveness of behavioral counseling incorporating assertive training techniques in enhancing achievement motivation and self-expression. The study employed a quantitative approach with a quasi-experimental design, utilizing a pretest-posttest control group design. The sample consisted of 60 students, divided into an experimental group and a control group. The intervention was given to the experimental group through behavioral counseling sessions based on assertive training. Data were collected using an achievement motivation questionnaire and a questionnaire about the need to express themselves, which had been tested for validity and reliability. Data analysis employed the MANOVA test after the prerequisite analysis tests were met. The results showed that assertive training techniques were significantly effective in improving both variables simultaneously (p < 0.05). These findings suggest that a behavioral approach based on assertive training can foster students' adaptive behavior, enhance self-confidence, and promote more optimal academic and social outcomes. The practical implications of this study indicate the need to integrate this technique into school counseling services to support the character formation and profile of Pancasila Students.